2010
DOI: 10.1016/j.virol.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of endogenous feline leukemia virus proliferation among species of the domestic cat lineage

Abstract: Endogenous feline leukemia viruses (enFeLVs) occur in the germ lines of the domestic cat and related wild species (genus Felis). We sequenced the long terminal repeats and part of the env region of enFeLVs in domestic cats and five wild species. A total of 305 enFeLV sequences were generated across 17 individuals, demonstrating considerable diversity within two major clades. Distinct proliferations of enFeLVs occurred before and after the black-footed cat diverged from the other species. Diversity of enFeLVs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
3
30
0
3
Order By: Relevance
“…Studies on endogenous feline leukemia viruses in the germ lines of the domestic cat and related wild species of the genus Felis revealed similar results to those describe in the current study, suggesting a complex history of interactions between FeLV and the germ lines of the species that comprise the domestic cat lineage (Polani et al, 2010). These findings are also analogous to the different patterns seen across species of primates in studies involving ERVs also found in humans (Bannert and Kurth, 2006).…”
Section: Evolutionary Dynamics Of Enjsrvssupporting
confidence: 87%
“…Studies on endogenous feline leukemia viruses in the germ lines of the domestic cat and related wild species of the genus Felis revealed similar results to those describe in the current study, suggesting a complex history of interactions between FeLV and the germ lines of the species that comprise the domestic cat lineage (Polani et al, 2010). These findings are also analogous to the different patterns seen across species of primates in studies involving ERVs also found in humans (Bannert and Kurth, 2006).…”
Section: Evolutionary Dynamics Of Enjsrvssupporting
confidence: 87%
“…In a study on the endogenous form of feline leukemia virus (enFeLV), which is a Gammaretrovirus , domestic and wild cats were analyzed to detect env-LTR and LTR sequences of enFeLVs [34]. No evident differences in the presence of enFeLVs were observed between domestic cat and its similar wild relatives [34].…”
Section: Presence Of Ervs In Domestic Animalsmentioning
confidence: 99%
“…No evident differences in the presence of enFeLVs were observed between domestic cat and its similar wild relatives [34]. In addition, the sequences of enFeLVs from the domestic cat and its nearest wildcat species ( F. silvestris and F. lybica ) clustered together; therefore, it seems that these copies were present before cat domestication and that there has not been any substantial activity since then [34]. …”
Section: Presence Of Ervs In Domestic Animalsmentioning
confidence: 99%
“…The endogenous counterparts of exogenous FeLV, termed enFeLVs, are integrated into the genomes of the Felis genus. Primary colonization of the feline germ line by FeLVs is believed to have occurred in an ancestor of the domestic cat after separation from the leopard lineage (2,11,31). Like most endogenous retroviruses, enFeLVs are noninfectious and nonpathogenic (4).…”
mentioning
confidence: 99%